Factors and Challenges in Using Gamification In Teaching ESP - Nusi, Ahmad; Dewirahmadanirwati, Dewirahmadanirwati; Novia, Novia; Ardi, Havid (Fakultas Sastra Universitas Ekasakti, 2024)
The purpose of this study is to detect the key issues and challenges faced by English lecturers in implementing gamification in teaching English for Specific Purposes (ESP). This study was a qualitative study with case study design. A number of 16 lecturers were participants of this study. The data was collected through structured interviews, and then analyzed the interview responses using content analysis. The result of the study shown that there were factors or issues such as the occurrence of problems like irregularities, objections, and challenges during the game, the creation of a negative competitive environment, the extension of the time allotted for the game, and the creation of a noisy environment were found to be challenges to the use of gamification in the classroom. In addition, technical difficulties and problems with digital games, lack of technology and internet, technology, screen, and game addiction, and health or psychological issues are some of the main reasons why lecturers do not use gamification in their ESP teaching.